1998
DOI: 10.2166/wst.1998.0789
|View full text |Cite
|
Sign up to set email alerts
|

Chemical description of extracellular polymers: implication on activated sludge floc structure

Abstract: Activated sludge extracellular polymers (ECP) were extracted either by sonication or a combination of sonication and cation exchange resin treatment (CER). The chemical composition of the aqueous extract was investigated by chromatographic analysis of amino acids and sugars after hydrolysis. Up to 70 to 80% of the total organic carbon (TOC) of ECP was characterized. Proteins were found to be the major constituent of ECP, which was confirmed by pyrolysis/GC/MS analysis. Sugar and protein analysis led to complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
119
1
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(134 citation statements)
references
References 0 publications
3
119
1
5
Order By: Relevance
“…It is considered as the "control method" because it is the less degradative technique and there is a common step of centrifugation in all other protocols investigated. -Sonication (Dignac et al 1998): Sludge samples were sonicated in 50-mL fractions at 37 W for 1 min using a Bandelin Sonopuls GM 70 with a M 73 probe. -Sonication and CER (Dignac et al 1998;Liu and Fang 2002): The sludge sample was sonicated as previously described (50-mL fraction, 37 W, 1 min).…”
Section: Eps Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is considered as the "control method" because it is the less degradative technique and there is a common step of centrifugation in all other protocols investigated. -Sonication (Dignac et al 1998): Sludge samples were sonicated in 50-mL fractions at 37 W for 1 min using a Bandelin Sonopuls GM 70 with a M 73 probe. -Sonication and CER (Dignac et al 1998;Liu and Fang 2002): The sludge sample was sonicated as previously described (50-mL fraction, 37 W, 1 min).…”
Section: Eps Extractionmentioning
confidence: 99%
“…-Sonication (Dignac et al 1998): Sludge samples were sonicated in 50-mL fractions at 37 W for 1 min using a Bandelin Sonopuls GM 70 with a M 73 probe. -Sonication and CER (Dignac et al 1998;Liu and Fang 2002): The sludge sample was sonicated as previously described (50-mL fraction, 37 W, 1 min). CER (Dowex 20-50 mesh, Na + form, Sigma-Aldrich) was then added (70 gCER g −1 sludge VSS), and the mixture was stirred 1 h at 600 rpm with an orbital shaker.…”
Section: Eps Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal components of activated sludge flocs are bacteria and extracellular polymers substances (EPS). Determination of the chemical composition of EPS has been the objective of many research papers (Frolund et al 1996;Dignac et al 1998;Sponza, 2003), thus proteins and carbohydrates have been identified as the principal components of EPS (Comte et al 2006). Considerably less attention has been devoted to the influence of macromolecular composition of sludge on anaerobic digestion.…”
mentioning
confidence: 99%
“…Dissolved oxygen concentration has been identified as an important parameter to control simultaneous nitrification, denitrification and nitrite accumulation in SBR (Pochana and Keller, 1999;Rhee et al 1997). Sludge macromolecular composition has been monitored in continuous activated sludge systems (Frolund et al 1986;Dignac et al 1998;Sponza, 2003), in order to determine the macromolecular composition of the EPS. To date the study of the relationship between SBR operating conditions and sludge macromolecular conditions have received little attention.…”
mentioning
confidence: 99%